Narcotics Anonymous. (NA World Services., 2008)
Narcotics Anonymous (NA) describes itself as a "nonprofit fellowship or society of men and women for whom drugs had become a major problem". Narcotics Anonymous uses a traditional 12 step model that has been expanded and developed for people with varied substance abuse issues. This work is the so-called "Basic Text" and is divided into two parts. Part 1 discusses the basics of the NA fellowship program and the twelve steps and traditions. Part 2 is composed of many personal recovery stories